Pengaruh Komunitas Online Terhadap Keputusan Pembelian Generasi Z - Saraswati, Alita; Putri, Adira Amanda; Sari , Yesyca Permata (Syntax Literate, 2025)
This study aims to analyze the influence of online communities on Generation Z’s purchasing decisions. Online communities serve as platforms for interaction that not only facilitate information sharing but also shape opinions, preferences, and consumer behavior. As digital natives, Generation Z is highly connected to social media and online platforms, making their purchasing decisions often influenced by recommendations, reviews, and trends within these communities. This research employed a quantitative approach by distributing questionnaires to Generation Z respondents actively engaged in online communities. The findings indicate that online communities significantly influence the process of information search, evaluation of alternatives, and purchasing decisions. These results suggest that online communities play a strategic role in shaping Generation Z’s consumer behavior, highlighting the need for companies to optimize their presence in digital spaces.